SURFACE STRATEGY TAXONOMY: ERROR ANALYSIS IN ACADEMIC WRITING - Heru Saputra (ETERNAL (English Teaching Journal), 2022)
This research aimed at describing the types of errors and their sources produced by 25 students of the Academic Writing Class of the Talent Scouting Program at IAIN Salatiga. This research used a qualitative method using students' writing assignments as the data source. The Theory of Surface Strategy Taxonomy was used in the data analysis. In finding the source of error, the researcher used comparative analysis. This study found four types of errors, with a total of 29 errors, including the omission 17 times, misinformation 5 times, addition 5 times, and misordering 2 times. Meanwhile, four error types were found for the source of errors: developmental or intralingual errors 14 times, unique errors 6 times, interlingual errors 2 times, and ambiguous errors 7 times.